S100A1: a multifaceted therapeutic target in cardiovascular disease - Rohde, David; Ritterhoff, Julia; Völkers, Mirko; Katus, Hugo; Parker, Thomas G.; Most, Patrick (Journal of cardiovascular translational research, 2010)
Cardiovascular disease is the leading cause of death worldwide, showing a dramatically growing prevalence. It is still associated with a poor clinical prognosis, indicating insufficient long-term treatment success of currently available therapeutic strategies. Investigations of the pathomechanisms underlying cardiovascular disorders uncovered the Ca2+ binding protein S100A1 as a critical regulator of both cardiac performance and vascular biology. In cardiomyocytes, S100A1 was found to interact with both the sarcoplasmic reticulum ATPase (SERCA2a) and the ryanodine receptor 2 (RyR2), resulting in substantially improved Ca2+ handling and contractile performance. Additionally, S100A1 has been described to target the cardiac sarcomere and mitochondria, leading to reduced pre-contractile passive tension as well as enhanced oxidative energy generation. In endothelial cells, molecular analyses revealed a stimulatory effect of S100A1 on endothelial NO production by increasing endothelial nitric oxide synthase activity. Emphasizing the pathophysiological relevance of S100A1, myocardial infarction in S100A1 knockout mice resulted in accelerated transition towards heart failure and excessive mortality in comparison with wild-type controls. Mice lacking S100A1 furthermore displayed significantly elevated blood pressure values with abrogated responsiveness to bradykinin. On the other hand, numerous studies in small and large animal heart failure models showed that S100A1 overexpression results in reversed maladaptive myocardial remodeling, long-term rescue of contractile performance, and superior survival in response to myocardial infarction, indicating the potential of S100A1-based therapeutic interventions. In summary, elaborate basic and translational research established S100A1 as a multifaceted therapeutic target in cardiovascular disease, providing a promising novel therapeutic strategy to future cardiologists.